POST-MENOPAUSAL WOMEN’S EXPERIENCE OF GREEN THERAPY (GUIDED IMAGERY, RESISTANCE EXERCISE, ESTROGENOUS NUTRITION) ON MENOPAUSAL SYMPTOMS AND QUALITY OF LIFE - A QUALITATIVE STUDY - Eswari. J, Dr. Hema V.H. (South Eastern European Journal of Public Health, 2025)
Background and Aim of the Study: Menopause is a natural biological process. Menopause marks the conclusion of the female reproductive cycle. Menopause occurs when the ovaries stop releasing the hormone. Hormonal changes during menopause cause a multitude of bothersome symptoms. These symptoms may interfere with women's quality of life. Every woman has spent the last three decades of her life in the postmenopausal stage. As a result, the total health and well-being of middle-aged women have emerged as a significant global public health priority. The most effective and risk-free way to treat hormone imbalances and menopausal symptoms is through complementary and alternative therapy, which includes mind-body therapy and botanical treatments. The main aim of the study is to explore the experience of menopausal women regarding GREEN therapy on menopausal symptoms and Quality of life. Materials and methods: The participants were 20 post-menopausal women who had practiced GREEN Therapy regularly. The researcher selected the study samples using the purposive sampling technique. The researcher conducted face-to-face, in-depth interviews, asking the study participants semi-structured probing questions about their experiences with GREEN therapy. Results: The results reveal three main themes and seven subthemes regarding the experiences of GREEN therapy among menopausal women. The researcher derived the themes from descriptive codes found in a significant portion of data. The themes include “Alleviation of Menopausal Symptoms and Life Satisfaction”, “Initial Behavioural Pattern and coping strategies”, “Acquaintance with GREEN Therapy” Conclusion: The study determined the experience of post-menopausal women after practicing GREEN therapy, and it also identified the difficulties of practicing the intervention and coping methods. The study's findings will assist health personnel in managing menopausal symptoms and preserving the quality of life of menopausal women without the need for hormonal treatments.